Respuesta :

Answer:

B is the answer

Step-by-step explanation:

The required explicit formula for the sequence is [tex]a_n = 9+(n+1)(-3)[/tex]. Option B is correct.

Given, an arithmetic sequance is given in the form of [tex]\left \{ {{a_1=9} \atop {a_n =a_{n-1}-3} \right.[/tex] .
Explicit formula for the sequence is to be determined.

What is arithmetic progression?

Arithmetic progression is the sequence of numbers that have common differences between adjacent values.
Example,  1, 2, 3, 4, 5, 6. this sequence as n = 6 number with a = 1 (1st term)  and common differene d = 2- 1 = 1.


Given arithmetic sequance is in the form of [tex]\left \{ {{a_1=9} \atop {a_n =a_{n-1}-3} \right.[/tex]
From above expression
[tex]a_n-a_{n-1}= -3[/tex]
common difference (d) = -3
with d = -3 and [tex]a_1 = 9[/tex]
The equation for the nth term in an arithmetic sequence is given by
[tex]a_n =a +(n-1)d[/tex]
[tex]a_n = 9 +(n-1)(-3)[/tex]
The above expression is the explicit form of the arithmetic equation.

Thus, the required explicit formula for the sequence is [tex]a_n = 9+(n+1)(-3)[/tex]. Option B is correct.

Learn more about arithmetic progression here:
https://brainly.com/question/20334860
#SPJ5

ACCESS MORE